Poorer Well-Being in Children With Misophonia: Evidence From the Sussex Misophonia Scale for Adolescents - Rinaldi, Louisa J.; Smees, Rebecca; Ward, Jamie; Simner, Julia (Frontiers in Psychology, 2022)
Objective Misophonia is an unusually strong aversion to a specific class of sounds -- most often human bodily sounds such as chewing, crunching, or breathing. A number of studies have emerged in the last 10 years examining misophonia in adults, but little is known about the impact of the condition in children. Here we set out to investigate the well-being profile of children with misophonia, while also presenting the first validated misophonia questionnaire for children. Methods We screened 142 children (10-14 years; Mean 11.72 SD 1.12; 65 female, 77 male) using our novel diagnostic (the Sussex Misophonia Scale for Adolescents; SMS-Adolescent). This allowed us to identify a group of children already manifesting misophonia at that age – the first population-sampled cohort of child misophonics examined to date. Children and their parents also completed measures of well-being (for convergent validation of our SMS-Adolescent) and creative self-construct (for discriminant validation). Results Data show that children with misophonia have significantly elevated levels of anxiety and obsessive compulsive traits. Additionally children with misophonia have significantly poorer life-satisfaction, and health-related quality of life. As predicted, they show no differences in creative self-construct. Conclusions Together our data suggest the first evidence in population sampling of poorer life outcomes for children with misophonia, and provide preliminary convergent and discriminant validation for our novel misophonia instrument. Our data suggest a need for greater recognition and therapeutic outlets for adolescents with misophonia.